Head injury with temporal bone fracture: one year review of case incidence, causes, clinical features and outcome - Asha'ari, Zamzil Amin; Razali, Mohd Sayuti; Abdullah, Kahairi; Wan Leman, Wan Ishlah; Raja Lope Ahmad, Raja Ahmad Al'konee (Malaysian Medical Associations, 2008)
To investigate the case incidence, causes, clinical profile and outcome of temporal bone fracture complicating head trauma. A 1-year (2005) retrospective study of head injured patients presented to the Emergency Department, Hospital Tengku Ampuan Afzan, Kuantan, Pahang, Malaysia. Gender distribution, cause of injury, radiological findings and otorhinolaryngological clinical presentations were analyzed. Of 1309 patients, 61 patients were diagnosed to have temporal bone fracture (4.7%). Majority of cases were caused by motor vehicle accident (85.9%) and were predominantly male (88.5%). The right temporal bone was more frequently fractured (62.3%). Most (88.5%) were petro-mastoid fractures. Sixty-seven percent of the petrous fractures were longitudinal type. Clinical presentations mostly reported were blood rhinorrhea (36%) and blood otorrhea (32.7%). Other clinical presentations were hearing loss (9.8%), cranial nerve palsy (8.2%), cerebrospinal fluid oto-rhinorrhea (8.2%) and labyrinth concussion (6.5%). Four out of five cranial nerve palsies were facial nerve. Out of the 61 cases, 16 (26.2%) had no clinical presentation at the time of Emergency Department consultation. Thirteen (21.3%) died due to severe head injury. The case incidence of temporal bone fracture in head injured patients in our centre is 4.7%. The petro-mastoid type fracture predominates. Proper early diagnosis and management minimize complications.